Flexibility provision by virtual power line and soft open point in AC/DC distribution systems - Xiaodong Yang; Wentao Jiang; Jing Ma; Da Xu; Chengjia Zhang; Yue Yang; Zhicheng Xu (International Journal of Electrical Power & Energy Systems)
The increasing penetration of photovoltaic generation will significantly challenge the voltage quality, power flow, power losses in active distribution networks. To address the voltage quality and operational efficiency issues caused by the high penetration of PVG, this paper fully explores the regulation potential of hybrid AC/DC distribution networks (HDNs) and electric vehicles (EVs). In this paper, a flexible scheduling model for HDN is proposed, incorporating soft open points (SOPs) and various types of EV charging stations. Firstly, a virtual power line model containing both fast charging station and slow charging station is established within HDN, enabling the effective utilization of their flexibility. Secondly, considering the coordination of SOP with on-load tap changers, energy storage systems, and other regulatory devices, a coordinated optimization model for fast charging station and slow charging station with SOPs is developed to minimize operational costs and alleviate voltage deviations for HDN. The model is converted into a mixed-integer second-order cone programming problem for solution through linearization and conic relaxation. Simulation results demonstrate that the proposed method effectively reduces overall operational costs, mitigates voltage issues associated with high PV integration, and enhances the PV accommodation capacity of the HDN.